2012
DOI: 10.1007/s00404-012-2222-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral estradiol and levonorgestrel on cardiovascular risk markers in postmenopausal women

Abstract: Hormone therapy using 1.0 or 0.5 mg of mE(2) and LNG lowers the serum levels of TC, HDL-C, LDL-C, and TG without significantly affecting coagulation/fibrinolysis parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
(30 reference statements)
0
11
1
5
Order By: Relevance
“…Estrogen therapy in post-menopausal women can, therefore, reduce cardiovascular disease. 23 While in the study reported here the magnesium level in peri-and post-menopausal women with periodontal diseases was lower than that of pre-menopausal women, it might occur in the serum of peri-and post-menopausal women. Hypomagnesia associated with estrogen deficiency and periodontal inflammation could cause reactive oxidative stress (ROS) accumulation that manifests itself in depressive syndrome.…”
Section: Discussioncontrasting
confidence: 56%
“…Estrogen therapy in post-menopausal women can, therefore, reduce cardiovascular disease. 23 While in the study reported here the magnesium level in peri-and post-menopausal women with periodontal diseases was lower than that of pre-menopausal women, it might occur in the serum of peri-and post-menopausal women. Hypomagnesia associated with estrogen deficiency and periodontal inflammation could cause reactive oxidative stress (ROS) accumulation that manifests itself in depressive syndrome.…”
Section: Discussioncontrasting
confidence: 56%
“…HT in younger women close to menopause is thought to be protective for coronary disease and total mortality 12 ; however, there are several possible mechanisms for this observation, and changes in lipids and coagulation markers have not been linked to beneficial events or AEs. Well-known metabolic changes with some oral HT formulations include decreases in total cholesterol and lowdensity lipoprotein-cholesterol (LDL), and increases in highdensity lipoprotein-cholesterol (HDL) and triglycerides [13][14][15][16] . Some oral HT formulations also cause an imbalance in hemostatic factors leading to blood coagulation activation and a hypercoagulable state [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Well-known metabolic changes with some oral HT formulations include decreases in total cholesterol and lowdensity lipoprotein-cholesterol (LDL), and increases in highdensity lipoprotein-cholesterol (HDL) and triglycerides [13][14][15][16] . Some oral HT formulations also cause an imbalance in hemostatic factors leading to blood coagulation activation and a hypercoagulable state [13][14][15][16][17] . Some progestogens attenuate the beneficial effects of estrogens on lipid metabolism, those with greater androgenicity having more impact [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…E 2 also has direct antioxidant effects (1), changes vascular reactivity (2,3), interacts with vascular smooth muscle (4,5), and reduces the level of circulating cholesterol (6) and free fatty acids (FFAs) (7). Some of these effects are acute, taking place within minutes or hours (8), whereas the beneficial effects on lipid metabolism may be related to more prolonged effects of E 2 on muscle and fat distribution.…”
Section: Introductionmentioning
confidence: 99%